ORGANIC PRODUCTION OF LAVENDER IN SERBIA - ECONOMIC AND FINANCIAL ANALYSIS - Kontic, Ljiljana; Zečević Stanojević, Olgica; Vasić, Mile (Economics of Agriculture, 2022)
The main aim of this study is to access possibilities of organic production of lavender in Serbia. As a result that 1999 and 2020 have been dubbed the “Year of Lavender” in the US, researchers and practitioners focused various aspects lavender production and cultivation. Lavender is an aromatic-medicinal plant, cultivated in Mediterranean region. The plants have used twofold: as an essential oil as well as a ﬂower. In this study, the authors use a comparative analysis and feasibility study as research methods. The results of comparative analysis revealed that the main countries in organic production of lavender were Bulgaria, France, China, Ukraine, Spain and Morocco. Also, the feasibility study in Serbia showed positive effect on organic lavender production in Serbia. This can be the case study for organic production of lavender to other farmers in Serbia. The limitations and future research agenda will be presented, too.